The illusionist : the true story of the man who fooled Hitler - Hutton, Robert (Pegasus Books, 2024)
"Cairo, 1942: If you had asked a British officer who Colonel Clarke was, they would have been able to point him out: always ready with a drink and a story, he was a well-known figure in the local bars. If you then asked what he did, you would have less success. Those who knew didn't tell, and almost no one really knew at all. Clarke thought of himself as developing a new kind of weapon. Its components? Rumour, stagecraft, a sense of fun. Its target? The mind of Erwin Rommel, Hitler's greatest general. Throughout history, military commanders have sought to mislead their opponents. Dudley Clarke set out to do it on a scale no one had imagined before. Even afterwards, almost no one understood the magnitude of his achievement. Drawing on recently released documents and hugely expanding on the louche portrait of Clarke as seen in SAS: Rogue Warriors, journalist and historian Robert Hutton reveals the amazing story of Clarke's A Force, the invention of the SAS and the Commandos, and the masterful hoodwinking of the Desert Fox at the battle of El Alamein. The Illusionist tells for the first time the dazzling tale of how, at a pivotal moment in the war, British eccentricity and imagination combined to thwart the Nazis and save innumerable lives - on both sides"--Publisher's description.